Intra-industry trade and industrial adjustment: the Irish experience - Brulhart, Marius; McAleese, Dermot (Economic & Social Studies, 1995)
This paper updates and extends previous studies of Irish intra-industry trade (IIT). The reported IIT proportions are calculated from the most comprehensive Irish trade data set used in this context to date, both in terms of time coverage and of statistical detail. Even at a five-digit level of industry disaggregation, 38 per cent of all trade and 44 per cent of trade in manufactured goods were found to be IIT in 1990. The stabilisation and partial decline of IIT levels in the 1980s, detected by earlier studies, is confirmed by reference to Grubel-Lloyd and Aquino-adjusted measures. This decline reflects a pattern of increased inter-industry specialisation instead of the trend towards higher intra-industry specialisation observed at the earlier stages of Irish trade liberalisation. Between 1985 and 1990, Irish industry specialised out of labour-intensive sectors into capital-intensive, export-oriented industries. As a result, growth of manufacturing employment (3 per cent) was considerably smaller than the increases in output (27 per cent) and trade volumes (33 per cent). This process of adjustment is analysed in detail, applying new methods of measuring marginal IIT on a set of matching trade and production data for Irish manufacturing. IIT is found to be associated with lower adjustment costs than inter-industry trade.
Keywords: Intra-industry trade; Industrial adjustment; Ireland